Buddhism in the Lanna Era in the 13th Century - Chitawan, Anan (BUDDHO, 2025)
This study examines the formative role of Theravāda Buddhism in the emergence and consolidation of the Lanna Kingdom during the thirteenth century. Focusing on the reign of King Mangrai and the foundation of Chiang Mai in 1296 CE, the research analyzes how Buddhism functioned not merely as a religious system but as a structural foundation for political authority, social organization, education, and artistic expression. Drawing upon historical, textual, and art-historical sources, the study demonstrates that the incorporation of Haripunchai’s Mon Buddhist heritage and the adoption of the Sri Lankan (Lankavamsa) ordination lineage were decisive in institutionalizing orthodox Theravāda Buddhism in Lanna. The findings reveal that the ideology of dhammarāja legitimized kingship through merit-making, temple patronage, and the protection of the Sangha, while monastic institutions became centers of literacy, scriptural transmission, and ethical formation. The development of Tai Tham script and palm-leaf manuscript culture further localized Buddhist knowledge and reinforced regional identity. Additionally, Lanna’s distinctive artistic and architectural forms embodied Buddhist cosmology and expressed the integration of religion with communal life. The study contributes new knowledge by demonstrating that political consolidation and religious institutionalization in Lanna were mutually constitutive processes. Buddhism operated as a comprehensive civilizational framework, structuring governance, education, moral economy, and cultural production. This integrated model of Buddhist statecraft provides important insights into the historical relationship between religion and political authority in mainland Southeast Asia.